Nilai-Nilai dalam Permainan Tradisional Banjar “Ba-u-upauan” sebagai Sumber Belajar Ilmu Pengetahuan Sosial - Noor Hidayati (IAIN Madura, 2021)
The success of education makes students better than before. The determining factor in the success of education is supported by the personality of the students. Personality is obtained by character values ​​that are instilled through the learning process. Through this learning resource, the traditional game